Google trends and online media data for supply and demand information in waste management evaluation in Jakarta - Robert Kurniawan; Agung Purwanto; Anugerah Karta Monika; Krismanti Tri Wahyuni; Muhammad Yunus Hendrawan; Mohamad Andrian Isnaeni (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Demand and supply of information in online media, particularly regarding waste management, remain hampered by a number of obstacles. Consequently, the objective of this study is to determine the public's interest in waste management knowledge based on demand data obtained from Google trends and to determine the most recent events in waste management by analyzing online news content. As a result, vector autoregressive (VAR) with impulse response function (IRF) and latent dirichlet allocation (LDA) are utilized as the analysis method. An important finding of this study is that it takes at least four weeks for individuals to absorb waste management information. Therefore, it is necessary for the government and the pentahelix component to sit together in order to reduce the community's information acquisition delay. Waste management, which is the subject of the shared information, should guide the selection of keywords by information providers.